Blood endocannabinoid levels in patients with panic disorder. (December 2020) - Petrowski, Katja; Kirschbaum, Clemens; Gao, Wei; Hardt, Jochen; Conrad, Rupert
Highlights: Higher endocannabinoid and N-acylethanolamine blood levels in patients with panic disorder compared to healthy controls. No main effects of panic disorder on the endocannabinoid (EC) stress reactivity to the TSST. 2-AG and N-acylethanolamines were significantly positively correlated with clinical measures of panic and anxiety. Abstract: Background: The development and maintenance of anxiety disorders is not fully understood. There is consensus in the literature that in addition to genetic factors, social, psychological and neurobiological factors are of crucial importance. The present exploratory study investigates the influence of the endocannabinoids (EC) and related N-acylethanolamines (NA) on the maintenance of panic disorder (PD). Methods: A total of n = 36 PD and n = 26 healthy controls (HC) were included in the study. Baseline characteristics showed no differences between the two groups. The participants were exposed to the Trier Social Stress Test (TSST) for reliable laboratory stress induction. Blood samples were taken during the TSST by an intravenous catheter to examine the endocannabinoid (EC) stress response. Repeated measures ANOVA was conducted to test for main effects of time and group as well as the respective interaction. Results: Participants with PD consistently had significantly higher EC and NA blood levels than HC. The consistently high EC and NA levels barely showed any reactivity as indicated by a lack of statistical variance. In line with these findings no reaction to the psychosocial stressor TSST could be detected. Conclusion: Our main results show significant differences in EC concentrations between participants with PD and HC. These findings suggest that an imbalance in the ECS contributes to the maintenance of PD. Increased endocannabinoid levels may have important implications for organic diseases such as cardiovascular disorders. The limitations of the study as well as implications for further investigations are discussed.